DEVELOPING THE LABOUR PARTY'S COMPREHENSIVE SECONDARY EDUCATION POLICY, 1950-1965: PARTY ACTIVISTS AS PUBLIC INTELLECTUALS AND POLICY ENTREPRENEURS. Issue 5 (3rd September 2022) - Rost, Anna Olsson; Collinson, Marc
ABSTRACT: The main aim of this article is to use the case study of comprehensivisation to examine the role of party activists as policy entrepreneurs and public intellectuals during the period 1950–1965. The intention is to widen the traditional notion of the public intellectual in order to better evaluate policy-making processes within the Labour Party. It will be argued here that these figures were also policy entrepreneurs, who actively created and advocated new policy solutions, not just unconnected idea merchants hawking impractical or ignorable ideas without a clear strategy. Previously, Labour policy on comprehensivisation was viewed as a 'missed opportunity', a case study of ambivalent policymakers lacking vision. However, this article demonstrates that, over a long period of time, a methodical policymaking process considered and adopted a position that advocated a more comprehensive schooling system. In this process, the sustained activities of Fabian Society and NALT members, acting as policy entrepreneurs within the Labour Party's policymaking organs to transform often non-committal and vague conference resolutions into a usable policy solution.